Students’ conceptual, representational, and analytical difficulties in balancing chemical equations: A thematic analysis - Olasunkanmi Moses Ogundiji; Mojeed Kolawole Akinsola; Dorcas Olufunke Moronkola; Ayodeji Nathaniel Omilani (International Journal of Mathematics and Sciences Education, 2026)
Balancing chemical equations (BCE) is foundational to chemistry learning, yet Nigerian secondary students persistently underperform on this skill. A companion quantitative survey drawn from the same population (Ogundiji, 2024) documented the prevalence of specific difficulties, for example that 96.56% of students could not correctly identify the limiting reagent and 79.3% could not determine atomicity, but its descriptive design could not explain the cognitive roots underlying these figures. The present study extends that work by qualitatively diagnosing why senior secondary students struggle with BCE, using a thematic-analysis design grounded in Braun and Clarke’s (2006) six-phase framework. From the same population of 188 Senior Secondary II students across six public schools in Ibadan, Nigeria, ten students representing the 95th and 5th score percentiles on a validated 10-item Chemical Equation Diagnostic Test were purposively selected for in-depth response analysis. Thematic coding, verified through inter-rater agreement (Cohen’s kappa = 0.70), generated three overarching themes: Conceptual Difficulties (seven codes, including limiting-reagent and valency misconceptions), Representational/Symbolic Difficulties (three codes, including subscript-coefficient confusion), and Analytical/Stoichiometric Reasoning Difficulties. Findings show that students’ errors were not merely procedural slips but reflected weak understanding of conservation of mass, chemical notation, and mole-ratio reasoning, patterns evident among both high- and low-scoring students. By moving beyond prevalence data to explain the reasoning behind each error type, this study contributes the first structured thematic error taxonomy for BCE in the Nigerian context, offering chemistry teachers a diagnostic framework for targeted remediation rather than generic reteaching.